(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Salmonellosis infection is caused by bacteria of the genus Salmonella. There are many pathways for the pathogenic bacteria to spread which is through contaminated food, water, and contact with animals. The research was conducted to detect Salmonella spp. carriage in free-living aquatic turtles and zoo turtles. Turtles are frequent inhabitants of zoos and the owners of a large number of bacteria in their outer skin and shell surfaces that under adverse conditions can multiply and lead to the development of infection. However, they are known to be a frequent source of Salmonella infection without showing signs of disease. The risk of human infection exists if personal hygiene is not followed after contact with a turtle. Identification of bacteria of the genus Salmonella, the main causative agent of the disease was determined by the standard method on chromogenic Salmonella LAB-Agarᵀᴹ (BIOMAXIMA, Poland) agar. The inoculation was incubated under aerobic conditions at 37 ± 1°C for 72 h. Serotype (D serotype) was determined by serotyping in 11 from 16 (68.75%) Zoo inhabitants but not found in 25 free-living turtles. Our present research is of theoretical and practical value for the study of free-living turtles as well as from the collections of zoos under protection in Latvia and Europe. It is necessary to remember the possibility of infection with pathogenic bacteria.